Transvenous Closure of Patent Foramen Ovale: Preliminary Results with a New Self-Expanding Nitinol Wire Mesh in a Swine Model. (20th August 2009) - Krizanic, F.; Sigler, M.; Figulla, H. R.
Abstract : Objectives . The transvascular closure of patent foramen ovale (PFO) with self-expanding devices carries the risk of left atrial thrombus formation related to material protruding into the left atrium. Thus, we developed a novel device with flat left atrial disc geometry. We evaluated feasibility, handling, and biocompatibility in a porcine animal model. Methods . Implantation of an Occlutech Figulla PFO device was performed in 10 mini pigs using fluoroscopy and intra-cardiac ultrasound after transseptal puncture of the interatrial septum. Angiographic follow-up was performed after six and twelve weeks. Results . Implantation was successful in 100%. There were no further implant related complications. One procedure related death occurred, as one animal died of ventricular tachycardia due to mispunture of the interatrial septum. Angiographic studies showed no residual shunt during follow-up. Histopathological evaluation could demonstrate partial neoendothelialization after 6 weeks with completion after 12 weeks. The devices were incorporated into connective tissue containing fibro muscular cells. An only mild inflammatory reaction was detected locally related to the polyester fibers. Conclusion . In terms of feasibility and handling, the new device does not seem to be inferior to other presently used implantation systems. Good biocompatibility was demonstrated with rapid and complete neoendothelialization.